Apostles of the Alps : Mountaineering and Nation Building in Germany and Austria, 1860-1939 - Keller, Tait (Book collections on Project MUSE., 2016)
"Though the Alps may appear to be a peaceful place, the famed mountains once provided the backdrop for a political, environmental, and cultural battle as Germany and Austria struggled to modernize. Tait Keller examines the mountains' threefold role in transforming the two countries, as people sought respite in the mountains, transformed and shaped them according to their needs, and over time began to view them as national symbols and icons of individualism"--